2013
DOI: 10.1016/j.physletb.2013.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Holographic insulator/superconductor phase transition with Weyl corrections

Abstract: We analytically investigate the phase transition between the holographic insulator and superconductor with Weyl corrections by using the variational method for the Sturm-Liouville eigenvalue problem. We find that similar to the curvature corrections, in p-wave model, the higher Weyl couplings make the insulator/superconductor phase transition harder to occur. However, in s-wave case the Weyl corrections do not influence the critical chemical potential, which is in contrast to the effect caused by the curvature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 57 publications
5
50
0
Order By: Relevance
“…It is found that Weyl corrections modify the critical temperature at which holographic superconductors occur [32] and changes the order of the phase transition of the holographic superconductor [33]. The effects of Weyl corrections on the phase transition between the holographic insulator and superconductor has been also investigated in [36]. Recently, we [37] studied the dynamical evolution of the electromagnetic perturbation coupling to the Weyl tensor in the Schwarzschild black hole spacetime and analyze the effect of the Weyl corrections on the stability of the black hole.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that Weyl corrections modify the critical temperature at which holographic superconductors occur [32] and changes the order of the phase transition of the holographic superconductor [33]. The effects of Weyl corrections on the phase transition between the holographic insulator and superconductor has been also investigated in [36]. Recently, we [37] studied the dynamical evolution of the electromagnetic perturbation coupling to the Weyl tensor in the Schwarzschild black hole spacetime and analyze the effect of the Weyl corrections on the stability of the black hole.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in Gauss-Bonnet gravity were presented in [26,30], the effects of the Weyl corrections on p-wave holographic phase transitions [27] were studied in [28]. The p-wave holographic superconductors in different gravity backgrounds [29], and in the presence of non-linear electrodynamics [31,32] and other non-trivial conditions [33][34][35] have been elaborated.…”
Section: Jhep03(2016)215mentioning
confidence: 99%
“…In the corresponding bulk spacetime, it was observed that the nonlinearity of the electromagnetic field can hinder the growing mode to appear in the scalar perturbation [67], which is consistent with the phenomenon on the boundary CFT. Other works on holographic dual models in the presence of nonlinear corrections to the Maxwell electrodynamics can also be found in [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. These discussions were concentrated on the equilibrium state both in the bulk and boundary.…”
Section: Jhep02(2016)116mentioning
confidence: 99%